Effect of the use of bone spreaders on the vertical bone gain in sinus floor elevation by transalveolar approache (Latakia University Journal -Medical Sciences Series, 2022)
Aim: The research aims to evaluate the effectiveness of the bone spreaders in maxillary sinus floor elevation By studying the amount of Intrasinus bone gain (IBG).Materials and Methods: The research sample consisted of 10 patients who underwent 12 surgeries to elevate the floor of the maxillary sinus by Transalveolar approache using of the bone spreaders in conjunction with the placement of dental implants. The amount of bone gain after 6 months were studied using cone beam computed tomography.Results: One Membrane perforation occurred once out of 15 cases, 8.33%. The implant survival rate during the follow-up period was 100%.The average of preoperative residual bone height was 6.53 mm while the average of postoperative bone height 6 months was 7.98 mm. The average of vertical bone gain is 1.44 mm (statistically significant).  Statistically strong correlation between the Implant protrusion length and the vertical bone gain, while we did not find a statistically significant relationship between the residual bone height and this gainConclusions: The Bone Spreaders are effective for maxillary sinus floor elevation by Transalveolar approache in conjunction with the placement of dental implants by securing a good bone gain.